2021
DOI: 10.3390/ijms22031268
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Pathway in Cancer

Abstract: Serotonin (5-hydroxytryptamine, 5-HT) is a biogenic monoamine produced from the essential amino acid tryptophan. Serotonin’s role as a neurotransmitter in the central nervous system and a motility mediator in the gastrointestinal tract has been well defined, and its function in tumorigenesis in various cancers (gliomas, carcinoids, and carcinomas) is being studied. Many studies have shown a potential stimulatory effect of serotonin on cancer cell proliferation, invasion, dissemination, and tumor angiogenesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 45 publications
0
60
0
4
Order By: Relevance
“…A highly significant observation is that a subset of cells showed higher levels of Glutamate, GABA, or 5-HT ( Figure 6 ). GABA, Glu, and 5-HT have been well characterized as neurotransmitters as well as neurotrophic factors that activate intracellular signaling pathway via the stimulation of specific sets of cell surface receptors [ 23 , 24 , 25 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. Evidence is emerging that they can elicit diverse non-neuronal response by stimulating their receptors in non-neuronal tissues and recent studies have shown that the extra-neuronal synthesis and release of neurotransmitters cells into the TME by the cancer cells promote tumorigenesis and tumor progression in many cancers [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A highly significant observation is that a subset of cells showed higher levels of Glutamate, GABA, or 5-HT ( Figure 6 ). GABA, Glu, and 5-HT have been well characterized as neurotransmitters as well as neurotrophic factors that activate intracellular signaling pathway via the stimulation of specific sets of cell surface receptors [ 23 , 24 , 25 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. Evidence is emerging that they can elicit diverse non-neuronal response by stimulating their receptors in non-neuronal tissues and recent studies have shown that the extra-neuronal synthesis and release of neurotransmitters cells into the TME by the cancer cells promote tumorigenesis and tumor progression in many cancers [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is emerging that they can elicit diverse non-neuronal response by stimulating their receptors in non-neuronal tissues and recent studies have shown that the extra-neuronal synthesis and release of neurotransmitters cells into the TME by the cancer cells promote tumorigenesis and tumor progression in many cancers [ 23 ]. While these transmitters have been shown to stimulate cell proliferation in different cancers [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ], identification of them as potential oncometabolites or their role as mediators of autocrine signaling in ovarian cancer is hitherto unreported. Our results, presented here indicate that the antagonists of these metabolism-derived ligands can effectively disrupt the autocrine signaling loop and inhibit ovarian cancer cell proliferation ( Figure 7 , Figure 8 , Figure 9 , Figure 10 and Figure 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…5-HT is a neuromodulator with neurotransmitter and neuroendocrine functions in cancer (Balakrishna et al, 2021). Meanwhile, it also regulates a variety of immune processes, such as immune cell chemotaxis, activation, proliferation, and cytokine secretion (Herr et al, 2017).…”
Section: Serotoninmentioning
confidence: 99%
“…The importance of the serotonin pathway in the context of enhancing oncogenesis has also increased significantly in recent years. The available data indicate an increased growth of cancer cells under the influence of serotonin in prostate cancer, breast cancer, small-cell lung cancer, colorectal cancer, cholangiocarcinoma, hepatocellular carcinoma, and glioma [232]. Moreover, the activity of this monoamine has been associated with an intensified epithelial-mesenchymal transformation process, increased cell migration abilities, and thus an increase in metastatic potential [233].…”
Section: Other Aspects Of Trp Metabolismmentioning
confidence: 99%